Identification and Characterization of Potato Zebra Chip Resistance Among Wild Solanum Species - Mora, Victoria; Ramasamy, Manikandan; Damaj, Mona B.; Irigoyen, Sonia; Ancona, Veronica; Avila, Carlos A.; Vales, Maria Isabel; Ibanez, Freddy; Mandadi, Kranthi K. (Frontiers in Microbiology, 2022)
Potato zebra chip (ZC) disease, associated with the uncultured phloem-limited bacterium, Candidatus Liberibacter solanacearum (CLso), is transmitted by the potato psyllid Bactericera cockerelli. Potato ZC poses a significant threat to potato production worldwide. Current management practices mainly rely on the control of the psyllid to limit the spread of CLso. The present study investigated new sources of ZC resistance among wild Solanum species. A taxonomically diverse collection of tuber-bearing Solanum species was screened, and one ZC resistant and three ZC tolerant accessions were identified among the 52 screened accessions. Further characterization of the resistant accession showed that the resistance was primarily associated with antibiosis effects due to differences in leaf trichome density and morphology of the wild accession, which could limit the psyllid feeding and oviposition. This germplasm offers a good resource for further understanding ZC and psyllid resistance mechanisms, contributing to potato breeding efforts to develop ZC resistance cultivars. Alternatively, it could be used as a potential trap crop to manage psyllid and control ZC disease.